DETERMINATION OF WEIGHT COEFFICIENTS OF MORAL AND PSYCHOLOGICAL STATE COMPONENTS OF SERVICEMEN OF MILITARY UNITS OF THE NATIONAL GUARD OF UKRAINE FOR CONVOYING, EXTRADITION AND PROTECTION OF THE ACCUSED FOR EXPERT ASSESSMENT - Voloshko, Serhii; Prykhodko, Ihor (Honor and Law, 2022)
Using the method of expert evaluation, the ranking of the components of the moral and psychological state of the military personnel of the units of the National Guard of Ukraine for escorting, extradition and protection of the accused was carried out, and the weight coefficients were determined. The proposed integrative approach for assessing the level of the Ministry of Defense of military personnel will allow, in a short time, more objectively and reliably, with maximum reliability, to carry out a quantitative and qualitative comparison of the individual self-assessment of the Ministry of Defense of a serviceman and the expert assessment of the unit commander or his deputy for work with personnel, and provide recommendations to the commander (chief) for making an informed decision on the involvement of a serviceman in the performance of a specific service-combat mission or the continuation of its implementation. It should be noted that the experts did not assess the level of the serviceman’s MPS on each individual indicator, as is done in the individual self-assessment of the serviceman using the questionnaire «Assessment of the moral and psychological condition of servicemen of the National Guard each component as a whole». This allows a more objective assessment of the generalized level of the military personnel, reduces the time for processing the data and will allow more targeted corrective work with personnel to increase the level of military personnel. Such an assessment of the moral and psychological state will help the commander (chief) to make an informed decision on the involvement of a serviceman in the implementation of a particular service and combat assignments or its continuation.